Using tasks and repair practices in the Malaysian L2 classroom - Ismail, Lilliati; Abd. Samad, Arshad (Springer, 2014)
This study investigated the potential of using tasks in the Malaysian classroom to facilitate second language (L2) learning, particularly amongst Form 6 (18-year-old) students in the Malaysian secondary school system. These students had undergone 6 years of primary education and 5 years of secondary education in Malaysian public schools. They obtained average to excellent results in the standardized national public school examination when they were in Form 5 to qualify for Form 6 education, which is equivalent to a pre-university programme. The current study carried out classroom-based research using two task types of differing reasoning demands and investigated the main and interaction effects of task reasoning demand (TRD) and learner repair practices on the successful resolution of errors. Using a repeated-measures counterbalancing design with two consensus tasks of differing levels of reasoning demands (+TRD and −TRD), the study investigated how learners recognise gaps in their language use, draw attention to these gaps through negotiation of form and repair practices and, consequently, provide modified output. The results show that repair practices and level of reasoning demand have significant effects on successful repair outcomes. The result could imply the need to create awareness about learner repair practices during learner–learner interactions as they could potentially lead to L2 development.